2021
DOI: 10.1021/acs.molpharmaceut.0c00911
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of Temozolomide-Conjugated Gold Nanoparticles Functionalized with Anti-EphA3 for Glioblastoma Targeting

Abstract: Glioblastoma multiforme (GBM) is a highly lethal and aggressive tumor of the brain that carries a poor prognosis. Temozolomide (TMZ) has been widely used as a first-line treatment for GBM. However, poor brain targeting, side effects, and drug resistance limit its application for the treatment of GBM. We designed a Temozolomide-conjugated gold nanoparticle functionalized with an antibody against the ephrin type-A receptor 3 (anti-EphA3-TMZ@GNPs) for targeted GBM therapy via intranasal administration. The system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…These nanocomposites were able to promote higher accumulation rate, lower drug resistance, and greater specificity of the drug targeting the glioma site, providing practically a robust candidate for GBM treatment via IN route. [ 125 ]…”
Section: Types Of Nps Developed For the In Delivery To The Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…These nanocomposites were able to promote higher accumulation rate, lower drug resistance, and greater specificity of the drug targeting the glioma site, providing practically a robust candidate for GBM treatment via IN route. [ 125 ]…”
Section: Types Of Nps Developed For the In Delivery To The Brainmentioning
confidence: 99%
“…delivery. Currently, there are few exciting translational application reports regarding PEG‐modified NPs in biomedical fields, namely, GBM treatment, [ 125 ] neuroprotection in PD, [ 140 ] and AD therapy. [ 141 ] Liu et al.…”
Section: Therapeutic Applications Of Modified Nps For Brain Diseasesmentioning
confidence: 99%
“…Quite a few proven preclinical successes of Eph inhibition in GB are published [ 334 , 335 , 337 , 343 , 344 , 345 ]. Importantly, co-targeting multiple Eph receptors might be necessary to achieve a therapeutic response [ 62 , 330 , 346 , 347 ].…”
Section: Receptor Tyrosine Kinase Inhibitors (Rtkis) For Gb Therapymentioning
confidence: 99%
“…They suggested that GNPs, with tunable size (1‐100 nm) and shapes (sphere, rod, star, and cube), can be synthesized in a more immunogenic form than large polymeric particles or liposomes (>100 nm) and synergically enhance antigen presentation. The intranasal route is also leveraged by Wang et al 92 to deliver temozolomide (TMZ) to the brain with improved brain targets, reduced haematologic toxicity, and less drug resistance (Figure 4d). GNPs are tropically co‐delivered with antibiotics to exhibit their intrinsic antimicrobial property.…”
Section: Deliverymentioning
confidence: 99%
“…(d) Temozolomide‐conjugated GNPs functionalized with anti‐EphA3 and their ability to induce tumour apoptosis. Reproduced with permission 92 . Copyright 2021, American Chemical Society.…”
Section: Deliverymentioning
confidence: 99%